ANALYSIS OF IJTIHAD METHOD AND ISTINBATH JURISPRUDENCE IN FATWĀ DEWAN SYARIAH WAHDAH ISLAMIYAH REGARDING THE USE OF ONLINE PAYMENT - Azwar Iskandar; Muhammad Yusram; Aswanto Muhammad Takwi Hede (IAIN Manado, 2020)
This study aimed to: (1) recognize the reason behind the fatwa of Sharia Council of Wahdah Islamiyah on the law of the use of GoPay and the like; (2) identify the method of ijtihad implemented by Sharia Council of Wahdah Islamiyah in issuing their fatwas; and (3) analyze the method of istinbath for the fatwa of Sharia Council of Wahdah Islamiyah on the law of the use of GoPay and the like. The research method used was descriptive-qualitative field research with a qualitative-descriptive approach with content analysis techniques approach, library research, and normative (juridical normative). The results show that Sharia Council of Wahdah Islamiyah issued a fatwa owing to the need of community, specifically cadres and followers of Wahdah Islamiyah in Indonesia. In their method of ijtihad, Sharia Council of Wahdah Islamiyah consider that the Koran, Sunnah, consensus, and qiyas are propositions agreed upon by the scholars of ahlussunnah wal jamaah. Each fatwa issued by Sharia Council of Wahdah Islamiyah is collective fatwa through a deliberation process in a closed meeting of the board. Sharia Council of Wahdah Islamiyah issued that the basic law of the use of GoPay and similar payment is permissible on condition that it fulfills the rules of the sharf (exchange of money), in which discounts obtained through GoPay payments and the like are considered athaya (gifts) which are permitted and are not considered benefit of receivables (usury).